2006
DOI: 10.1055/s-2005-837621
|View full text |Cite
|
Sign up to set email alerts
|

The Intensity Level of Physical Exercise and the Bone Metabolism Response

Abstract: This study investigated the short-term effects of the intensity level of physical exercise on bone metabolism and related hormones. The responses of calciotropic hormones and bone biochemical markers were evaluated in seven male cyclists (mean age 24.4 years, range 20-39) during two 50-min cycling tests performed 15% below (-VT) and 15% above (+VT) the ventilatory threshold. In each test, venous blood samples were drawn at rest, at the 30th and 50th min of exercise, and after 15 min of recovery. For both inten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
75
6
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(85 citation statements)
references
References 26 publications
3
75
6
1
Order By: Relevance
“…However, TEE was fairly similar within subjects between days as reflected by a low within-subject CV (6.7%), despite a marginally lower TEE on day 3 because of cyclists being fatigued and exercising at an average 9% lower intensity on day 3 compared with the other days. Previous studies have observed changes in serum bone markers following a single bout of cycling only at moderate to high intensities and not at lower intensities where exercise persisted for up to only 1 h long (Herrmann et al 2007;Maïmoun et al 2006). However, the increment between the high and low exercise intensities in those previous studies was far greater (ϳ30% difference between intensities) than the small 9% decrease in intensity on day 3 of the current study.…”
Section: B † † †contrasting
confidence: 65%
See 2 more Smart Citations
“…However, TEE was fairly similar within subjects between days as reflected by a low within-subject CV (6.7%), despite a marginally lower TEE on day 3 because of cyclists being fatigued and exercising at an average 9% lower intensity on day 3 compared with the other days. Previous studies have observed changes in serum bone markers following a single bout of cycling only at moderate to high intensities and not at lower intensities where exercise persisted for up to only 1 h long (Herrmann et al 2007;Maïmoun et al 2006). However, the increment between the high and low exercise intensities in those previous studies was far greater (ϳ30% difference between intensities) than the small 9% decrease in intensity on day 3 of the current study.…”
Section: B † † †contrasting
confidence: 65%
“…which is greater than the 17%-46% increase reported in previous studies (Barry et al 2011;Guillemant et al 2004;Herrmann et al 2007;Maïmoun et al 2006). This discrepancy may be due to the 3-fold longer duration of cycling in the current study.…”
Section: B † † †contrasting
confidence: 61%
See 1 more Smart Citation
“…Prolonged, endurance exercise increases P-CTX [15][16][17][18][19] but again, bone formation markers are largely unresponsive [15,16,18,19], suggesting that prolonged exercise might result in a transient negative remodelling balance. This acute response may be of significance to athletic populations as the net effects of changes in bone resorption and formation have been implicated in both stress fractures [20] and changes in bone mineral density (BMD) [21].…”
Section: 3mentioning
confidence: 99%
“…20 However, a small study on seven competitive road cyclists in the south of France identified adequate mean 25(OH)D levels of 32.4 mcg/l. 33 While there are limited data on the effects of vitamin D deficiency on performance in athletes, the potential relationship with fracture risk [34][35][36] and altered muscle function, 37,38 in addition to the additional pathological associations noted above, would suggest that the identification and subsequent treatment of vitamin D deficiency in athletes is prudent. In the UK, track and field athletes would appear to be at significant risk of deficiency given the UK latitude (51 -54°N), the indoor training environment and the proportion of dark-skinned athletes in the elite UK Athletics Track and Field team.…”
Section: Introductionmentioning
confidence: 99%